Establishment and practice of the gynecology Traditional Chinese Medicine nursing clinic based on the concept of medical and nursing integration (基于医护一体化的妇科中医护理专科门诊建设与实践) - LI Shasha (李莎莎); LIU Ying (刘颖); ZHU Lei (朱磊); LIU Jing (刘静); LU Ying (卢英) (Association of Integrative Nursing, 2022)
The Department of Gynecology of Dongfang Hospital of Chinese Medicine has established a gynecology Traditional Chinese Medicine nursing specialist clinic, carried out a variety of TCM characteristic nursing projects, integrated the concept of medical and nursing integration into the construction of gynecology TCM nursing specialist clinic, and formed a gynecology integrated medical care model with TCM characteristics. The nursing clinic formulates the nursing plan and health education plan from three aspects: prevention before disease, prevention after disease and recovery after disease. On the basis of doctors' physique identification, the external treatment methods of traditional Chinese medicine represented by ear point treatment and acupoint application are comprehensively applied to help patients recover their health as soon as possible, so as to promote the development of traditional Chinese medicine nursing, improve the ability of TCM nursing service and highlight the characteristics of TCM. (妇科中医护理专科门诊, 是将医护一体化理念融入到妇科中医护理专科门诊的建设中, 开展多种中医特色护理项目, 形成具有中医特色的妇科整体化医护模式。护理门诊从"未病先防, 已病防变, 病后防复"三方面制定护理方案及健康教育计划, 在医师体质辨识的基础上, 综合应用以耳穴治疗、穴位贴敷为代表的中医外治手法, 帮助患者尽快恢复健康, 以推动中医护理事业的发展, 提升中医护理服务能力, 彰显中医特色。)